2008
DOI: 10.1096/fj.07-105221
|View full text |Cite
|
Sign up to set email alerts
|

Adverse functions of IL‐17A in experimental sepsis

Abstract: IL-17A is a proinflammatory cytokine produced by a variety of cells. In the current study, we examined the role of IL-17A in sepsis induced in mice by cecal ligation and puncture (CLP). IL-17A levels, which rose time-dependently in plasma after CLP, were not affected in the absence of alphabeta T cells or neutrophils. In sharp contrast, gammadelta T cell-knockout or gammadelta T cell-depleted mice displayed baseline IL-17A plasma levels after CLP. Neutralization of IL-17A by two different antibodies improved s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
198
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 181 publications
(213 citation statements)
references
References 45 publications
11
198
2
2
Order By: Relevance
“…IL-17 plays an important pathogenic role in sepsis [9]. To demonstrate the role of IL-17-expressing gd T cells in the development of sepsis, here both mild grade sepsis and high grade sepsis models were used.…”
Section: Il-17 Was Secreted Mainly By CD T Cells In Clp-induced Sepsismentioning
confidence: 99%
See 3 more Smart Citations
“…IL-17 plays an important pathogenic role in sepsis [9]. To demonstrate the role of IL-17-expressing gd T cells in the development of sepsis, here both mild grade sepsis and high grade sepsis models were used.…”
Section: Il-17 Was Secreted Mainly By CD T Cells In Clp-induced Sepsismentioning
confidence: 99%
“…IL-17 (also known as IL-17A) is a proinflammatory cytokine produced by a variety of cells including CD4 1 Th17 cells, CD8 1 T cells, neutrophils and NK cells [8]. Recent reports also suggested that gd T cells are a major source of IL-17 [9]. Although it has been demonstrated that IL-17 plays an important role in defense against extracellular pathogens such as Klebsiella pneumoniae [10], production and regulation of IL-17, interaction of IL-17 with other critical pro-inflammatory cytokine in sepsis, remain largely unclear.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, other authors demonstrated that the blockage of IL-17A was protective in cecal ligation and puncture (CLP)-induced sepsis. These authors associated the protective effects of IL-17A blockade with a reduction in the levels of bacteremia and of systemic proinflammatory cytokines and chemokines (41).…”
Section: Il-17 Receptor Signaling Is Required To Controlmentioning
confidence: 99%